Efforts of the United Arab Emirates to preserve the cultural and architectural heritage based on international conventions and standards for preserving cultural heritage: The case study of Al-Jazirah Al-Hamra - AL Shikh Warak, Mahmoud; Jamhawi, Monther (Al-Adab Journal, 2023)
Ras al-Khaimah is one of the largest cities in the United Arab Emirates. The emirate is famous for its rich history and heritage, as it was one of the most important commercial centers in the Gulf in the past. It was famous for its fishing, extraction and trade in precious pearls. Al-Jazirah Al-Hamra was one of the most important historical villages of the Emirate, which had a prominent place in pearl hunting and trade. It contains many historical houses and Dhayah Castle dating back to the eighteenth century AD. Despite the efforts of the Emirate of Ras Al Khaimah to preserve and develop Al Jazeera Al Hamra, these efforts have not been studied and evaluated. Therefore, this research deals with an evaluation of national efforts and interventions in preserving one of the heritage monuments in the Emirate of Ras Al Khaimah, which is Al Jazeera Al Hamra, as one of the cultural and heritage monuments that are importantly linked to the cultural, political and economic history of the region and its prominent role in its presence within the history of the region and its impact extending beyond that as it was an extension for man in that not so distant era and his role in preserving man and history. An evaluation approach was used based on the standards of conservation and restoration of international conventions. After the evaluation process, the study concluded that the preservation and restoration process was largely successful in rehabilitating Al-Jazirah Al-Hamra and reusing some of its heritage places. The preservation process also contributed to conveying the idea of ​​the place and highlighting the cultural and national identity of the island.